PERANAN DAKWAH DALAM MEDIA WEBSITE DAN PENGARUHNYA DI MASYARAKAT - Hijaz Tahir Hijaz Tahir; Syamsu Tang; Saifullah Saifullah (JIA: Jurnal Ilmiah Administrasi, 2020)
Abstract The Western world, communication technology and mass media, have a big hand in building and establishing the moral principles of society. Internet media in particular, have a major role in introducing new norms of society. For the Islamic Ummah it is necessary to strengthen the missionary motivation which takes up so much time and attention of the majority Muslim community. Even now the technological means have been dubbed by the people of various terms for example, as a corona screen, a magic box, a window to the world and so on. The rapid introduction of new norms was made possible because the media moved with the principle of freedom of expression without preaching motivation, so that these principles were often used as a pretext for pursuing worldly interests. Unfortunately, many developing countries, including those claiming to be Muslim countries, follow this trend. As a result, Muslims around the world have been trapped in a foreign conceptual framework, which resulted in a media invasion of their value system, ethical perceptions, moral standards, sociocultural views, and even their religious beliefs. Therefore, Islam needs to set a da'wah strategy in all aspects of life through communication systems, especially electronic media that affect many people. This should not be ignored, and must be directed in accordance with Islamic perinsif which covers all aspects of life through the da'wah strategy. Technological development cannot be dammed. The role of Muslim communicators must defend the truth so that justice remains upheld. Justice cannot possibly be upheld without safeguarding the truth and this is the main task for the Islamic Ummah to carry out scientific charity including one of which is the application user in the mass media. Keywords ; Da'wah, technology, mass media